Loan demand and rationing among small-scale farmers in Nigeria - Gyimah-Brempong, Kwabena; Olomola, Aderibigbe (International Food Policy Research Institute, 2014)
To this end, this study seeks to (1) examine the nature of risks facing small-scale farmer-borrowers in Nigeria, (2) analyze the demand for agricultural credit by farmers and highlight the key determinants of this demand, (3) ascertain the extent to which farmers are credit rationed and the factors influencing the emerging rationing scenarios, and (4) suggest policy measures to address the problem of agricultural credit rationing and enhance the demand for credit. The study employs primary data obtained from 1,200 small-scale farmers through a survey conducted in 2013 across the six geopolitical zones of the country. Methodologically, the study extends the analysis of credit rationing beyond quantity rationing and presents explicit econometric models for analyzing the determinants of three types of credit rationing: quantity rationing, risk rationing, and price rationing.